BERFUNGSINYA JALAN TOL PEKANBARU-DUMAI TERHADAP DAMPAK SOSIAL EKONOMI MASYARAKAT KELURAHAN TANJUNG PALAS KECAMATAN DUMAI TIMUR RT 05 - Nasya Okta Nurtiana; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine the socio-economic impact of the community on the functioning of toll roads. the method used is descriptive quantitative. The formulation of the problem in this study (1) How is the socio-economic impact felt by the community with the opening of the Pekanbaru Dumai Toll Road? (2) ) What areas are seen and developed by the community? Data collection techniques in this study were in the form of questionnaires and documentation. This research was conducted in Tanjung Palas Village, East Dumai District with a total of 66 respondents using a random sampling technique. , the religion of the most respondents is Muslim as many as 54 people with an accumulation of 81.8%, the majority of respondents' education is high school with a total of 43 people or equivalent to 65.2%, and the length of stay of respondents in the research area varies, in the range above 5 years as many 54 people with an accumulation of 81.1%. In addition, the socio-economic impact is divided into 3, namely the type of work, which dominates the self-employment of 43 people or 65.2%, the level of income that dominates the average monthly income of the respondents, namely Rp. 1,000. 000-2,000,000. with an accumulation of 63.6% and ownership of wealth which dominates the majority, the people obtain land ownership rights by buying 49 people or 74.2%. Keywords: impact, tollroad, socio-economic